Análise de índices de extremos climáticos de temperatura do ar na Amazônia - Joseph, Wisnel (2020)
Currently, the Brazilian Amazon is the subject of major scientific and political debates around the world related to land use and occupation in the era of climate change. The objective of this work was to verify if there are changes in the trends of climate change detection indices derived from the maximum, average and minimum temperatures in Conventional Meteorological Stations (CMS), distributed in the inclusive Amazon biome, to look for associations between the changes in the series of air temperature and SST (Sea Surface Temperature) anomaly events of different phases and / or intensities. These CMS belong to the National Institute of Meteorology (NIM) network and have data available in the MDTR (Meteorological Database for Teaching and Research). The RCLIMDEX 1.9.0 software has been employed to numerically define 16 free climate change detection indices recommended by the Climate Change Detection Monitoring and Indices (CCI / CCLIVAR) available for download from the ETCCDMI website (http: // cccma. seos.uvic.ca/ETCCDMI/). For statistical analysis, the linear trend of the series (obtained by the least squares method), level of significance (p value), trend statistics, coefficient of determination (R2) and standard error of the estimate were considered as indicative. In this case, only linear trend (positive or negative) higher than the standard error of estimation and significant at p <0.1 were considered. Examination of the index results showed a warming over the years throughout the Amazon. There were increasing trends in TMAX and TMIN indices with even more significant trends in TMIN. There was an increase in the percentages of warm days and nights (TN10P, TN90P) and a decrease in the percentages of cold days and nights (TX10P, TX90P) in much of the Amazon. Indicators of summer days (SU25) and tropical nights (TR20) such as TNX, TXN, TXX, TNN, DTR showed changes in trends in most of the Amazon with more significant results for TR20. In the state of Pará, there was a significant decrease in DTR trends, indicating an increase in the minimum temperature at a rate higher than the maximum temperature. These changes can be of human causes in deforestation, urbanization, population growth, heat island formation, transportation and others. In addition, they may be causes of anomalies reported in the Equatorial Pacific Ocean SST through El Niño and La Niña since most indices showed mostly positive correlations in recent El Niño episodes.